Al confine tra ufficialità e underground. Forme di istituzionalizzazione della ‘seconda cultura’ sovietica - Alice Bravin (eSamizdat)
From the second half of the 1970s, some organizations of unofficial and independent artists and writers were created in the Soviet Union, which were officially recognized by Soviet authorities: in 1976 in the Moscow City Committee of Graphic Artists a section of painting was set up that united non-formal artists who exhibited their works in the halls in Malaia Gruzinskaia street; in 1981 in Leningrad the literary club “Klub-81” was created, a unique organization of unsanctioned writers under the direct control of the KGB; in 1985 an alternative literary association, the “Klub Poeziia”, was also founded in Moscow. These institutions represented a forum for discussions and interaction between the members of the unofficial culture, but at the same time they were under the jurisdiction of Soviet law and combined functions and features like any other official Soviet institution. The aim of this paper is to investigate the role and structures of these ambiguous and alternative organizations, on the border between official and non-official culture.